Realization of Stable Trajectory in Mass Measurement System Using Relay Feedback of Velocity and Restoring Force Compensation - Takeshi Mizuno; Keisuke Nishizawa; Masaya Takasaki; Yuji Ishino; Masayuki Hara; Daisuke Yamaguchi (SICE Journal of Control, Measurement, and System Integration, 2019)
A mass measurement system using relay feedback of velocity was developed. In this system, the velocity of the object was fed back through a relay with hysteresis. Although the efficacy of the proposed method has been already confirmed experimentally, it was subject to a drift mainly because only the velocity was fed back. To prevent such a drift, a spring element was added to produce restoring force. However, smaller drifts still occurred, and the trajectory of the object fluctuated. To eliminate such fluctuations, intermediate control is introduced. It succeeds to eliminate fluctuation of the trajectory in the developed apparatus.